2020
DOI: 10.3389/fcomm.2020.596663
|View full text |Cite
|
Sign up to set email alerts
|

Parasocial Relationships With President Trump as a Predictor of COVID-19 Information Seeking

Abstract: As the number of COVID-19 cases climbed in the United States, President Trump came under fire for dismissing its severity despite evidence to the contrary. Those most impressionable by the President's claims might be those who have established a parasocial relationship with him. Results of this survey study indicate that each of the three parasocial variables assessed (i.e., friends, understanding, and brand), were negatively related to information seeking for COVID-19. Moreover, initial evidence was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In their examination of the role of political ideology in consumer reaction to multiple consumption regulations (e-cigarettes, food warning labels, and using mobile phones while driving), Irmack and others (2020) found that the position held by the political party that subjects support affects how they cognitively and affectively process information presented to them about an issue. Moreover, numerous studies demonstrate that political ideology is a key contributor to individuals' attitudes about the level of threat attributed to the COVID-19 virus (Cakanlar et al, 2020;Kelly et al, 2020;Nowlan and Zane 2020;Roozenbeek et al, 2020;Van der Linden et al, 2020), as well as the efficacy of the vaccine (Bechler and Tormala, 2020;Chou and Budenz, 2020;Tyson et al, 2020).…”
Section: Political Ideologymentioning
confidence: 99%
See 2 more Smart Citations
“…In their examination of the role of political ideology in consumer reaction to multiple consumption regulations (e-cigarettes, food warning labels, and using mobile phones while driving), Irmack and others (2020) found that the position held by the political party that subjects support affects how they cognitively and affectively process information presented to them about an issue. Moreover, numerous studies demonstrate that political ideology is a key contributor to individuals' attitudes about the level of threat attributed to the COVID-19 virus (Cakanlar et al, 2020;Kelly et al, 2020;Nowlan and Zane 2020;Roozenbeek et al, 2020;Van der Linden et al, 2020), as well as the efficacy of the vaccine (Bechler and Tormala, 2020;Chou and Budenz, 2020;Tyson et al, 2020).…”
Section: Political Ideologymentioning
confidence: 99%
“…Research on the psychological foundations of attitude certainty suggest that factors such as information-seeking behavior (Kelly et al, 2020), having direct experience with the issue (Wu and Shaffer 1987); perceiving social support for one's attitude (Visser and Mirabile 2004), and the frequency of expressing an attitude about the issue (Holland et al, 2003) all contribute to attitude certainty. Moreover, the so-called "bandwagon effect" (an individual's tendency to adopt a particular style, behavior or attitude because they believe everyone else is doing it), can strengthen or weaken attitude certainty (Li and Sundar 2021).…”
Section: Institutional Trust and Attitude Certaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Studying people's information seeking behaviors amid the COVID-19 has become an urgent research topic in the latest LIS literature (Ali et al, 2020;Kelly et al, 2020;Li and Zheng, 2020;Moreno et al, 2020;Superio et al, 2021;Zimmerman, 2021). While some of these studies focus on older adults, only a handful to date have focused on older adults from a non-healthspecific perspective.…”
Section: Studies Of Information Sources During Public Health Crisesmentioning
confidence: 99%
“…Parasocial relationships also influence information seeking. Parasocial relationships with the former president of the United States of America, Donald Trump, were negatively related to information seeking for Covid-19 (Kelly 2020 ). The stronger the parasocial relationship, the weaker the information seeking.…”
Section: Introductionmentioning
confidence: 99%